2005
DOI: 10.1186/1479-5876-3-6
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes among HIV-infected and -uninfected infants: CD4/CD8 ratio as a potential tool in diagnosis of infection in infants under the age of 2 years

Abstract: Background: Serologic tests for HIV infection in infants less than 18 months do not differentiate exposure and infection since maternally acquired IgG antibodies may be detected in infants. Thus, the gold standard for diagnosis of HIV-1 infection in infants under the age of 2 years is DNA or reverse transcriptase polymerase chain reaction. There is an urgent need to evaluate alternative and cost effective laboratory methods for early diagnosis of infant HIV-1 infection as well as identifying infected infants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Clinical studies have demonstrated the use of the CD4/CD8 ratio as an indicator of immunocompromise in HIV-infected individuals, with high sensitivity (98%) and specificity (Ͼ98%), particularly for children Ͻ2 years of age (55,56). However, a recent study by Leung et al concluded that CD4/CD8 ratio normalization might not have additional short-term predictive value for clinical outcomes after accounting for other risk factors, such as age and HIV load (57).…”
Section: Discussionmentioning
confidence: 90%
“…Clinical studies have demonstrated the use of the CD4/CD8 ratio as an indicator of immunocompromise in HIV-infected individuals, with high sensitivity (98%) and specificity (Ͼ98%), particularly for children Ͻ2 years of age (55,56). However, a recent study by Leung et al concluded that CD4/CD8 ratio normalization might not have additional short-term predictive value for clinical outcomes after accounting for other risk factors, such as age and HIV load (57).…”
Section: Discussionmentioning
confidence: 90%
“…Perturbations of T cell subsets in severe malarial anemia and uncomplicated malaria resulted in increased proportions of children with reversed CD4/CD8 ratios (ratio of <1.0). Such a result has been proposed as a surrogate for HIV infection in African children ( 26 ). Therefore, the CD4/CD8 ratio should not be used in this way in the presence of active clinical infections, particularly malaria.…”
Section: Discussionmentioning
confidence: 99%
“…A CD4:CD8 T-lymphocyte ratio less than 1.0 is associated with HIV infection and has been proposed as a parameter for the diagnosis of HIV in African children under 18 months old, 32 where results of HIV rapid tests can be complicated by maternal antibody to HIV. 10,32 With decreased CD4 + and increased CD8 + T-lymphocyte concentrations in young children in this study compared with results from developed countries, 13% of Malawian children under 18 months had a CD4:CD8 ratio <1.0. Therefore, a CD4:CD8 ratio <1.0 is not specific for HIV infection, and this parameter should be used with caution in HIV diagnosis.…”
Section: Discussionmentioning
confidence: 99%